Financing System and Mechanism at Sharia Pawnshops - Sri Artati Salju; Mukhtar Lutfi; Lince Bulutoding (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
Sharia Pawnshop is one of the non-bank financial institutions that provides financing services based on sharia principles through the application of rahn and ijarah contracts. This research aims to analyze the financing system and mechanism in Sharia Pawnshops and identify the sharia principles applied in each financing process. The research uses a qualitative approach with the library research method. Data was obtained from various secondary sources, including scientific journals, books, fatwas of the National Sharia Council-Indonesian Ulema Council (DSN-MUI), regulations of the Financial Services Authority, and official documents related to Sharia Pawnshops. Data analysis is carried out using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the Sharia Pawnshop financing system is implemented transparently through the stages of financing application, collateral valuation, contract implementation, fund disbursement, storage of collateral, to repayment or auction in accordance with sharia provisions. All of these mechanisms prioritize the principles of justice, benefit, and freedom from the elements of usury, gharar, and maysir. Thus, Sharia Pawnshops are an alternative financing that is safe, accessible, and in accordance with Islamic economic values in supporting the increase of Islamic financial inclusion in Indonesia.